Implementasi Pendidikan Multikultural Siswa Dalam Pembelajaran Pendidikan Agama Islam Di SMP IT al-Miftah Kabupaten Karawang - Inayatullah, Encep; Astuti Darmiyanti; Ferianto (AL MURABBI, 2022)
The purpose of this study was to find out the forms and values of multicultural education in Islamic religious education learning at SMP IT Al-Miftah, Karawang Regency and to find out the Implementation of Multicultural Education in Islamic religious education learning at SMP IT Al-Miftah, Karawang Regency. This study uses qualitative data. Research data obtained by observation, interviews, and documentation. The analysis technique uses inductive and deductive methods. The results showed that teachers of SMP IT Al-Miftah, Karawang Regency had implemented multicultural education in Islamic education materials. The application is through adding themes or incorporating multicultural values in Islamic religious education material that already exists at SMP IT Al-Miftah, Karawang Regency. And the teaching is done in a thorough and in-depth way. Thus, multicultural education in Islamic religious education material is very important to apply. This is to anticipate the reality of pluralism that exists in society. Where the application of values in Islamic religious education material is carried out in order to help create peace or tolerance in the midst of the plurality of society itself.